The provision of global public goods: a game-theoretic comparison of international environment and knowledge. (1st January 2011) - Chou, P. Ben; Sylla, Cheickna
This paper provides a game theory perspective in comparing and contrasting the provision of international environment and knowledge as global public goods (GPGs). Because GPGs have the properties of non-rivalry in consumption and non-excludable access, the latter usually causes the free rider problem, and thus the under-provision of GPGs. From a game theory perspective, such a problem is similar to the multiple-player prisoners' dilemma. To resolve the under-production problem in international environment, a sufficiently large number of countries must be willing to participate in the international environmental agreement (IEA). It is also possible for all the countries to participate in the IEA, if the developed countries are willing to offer the technology transfers and finance assistance to the developing countries. To resolve the under-provision problem of knowledge creation, countries can resort to limiting the access to the knowledge with an access fee based on intellectual property rights (IPRs). However, stronger IPRs may also widen the knowledge gap between the developed countries and developing countries since most of the knowledge creation occurs in the developed countries. The paper also provides a number of possible solutions to improve international cooperation as well as the directions for future research.